Biodefense and special pathogen vaccines in development 1 - Kovacs, Gerald (Henry Stewart Talks, 2015)
Brief history of bioterrorism, Bioterrorism agents, Types of vaccines, Vaccine development: special requirements, Unique aspects of biodefense vaccines